2009
DOI: 10.1177/1066896908331231
|View full text |Cite
|
Sign up to set email alerts
|

XpII.2 Translocation Renal Carcinoma With Placental Metastasis: A Case Report

Abstract: Renal cell carcinomas with sporadic Xp11.2 translocations are uncommon malignancies in children and young adults associated with several different reciprocal translocations involving the TFE3 gene located on chromosome Xp11.2. Placental metastases are extremely rare, with only a handful of cases reported. This study reports the case of a 20-year-old woman with an Xp11.2 translocation renal carcinoma that metastasized to the placenta. This is the first reported case of a renal cell carcinoma metastatic to the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 14 publications
0
13
0
Order By: Relevance
“…To the best of our knowledge, the case herein presented is the first report of Xp11.2 translocation RCC occurring during pregnancy. Bovio et al [ 23 ] recently reported the case of a 20-year-old pregnant female with placental, bone and retroperitoneal lymph node metastases two years after radical nephrectomy for Xp11.2 translocation RCC, but no evidence of fetal metastasis. Hence, the initial diagnosis of Xp11.2 translocation RCC occurred prior to her pregnancy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To the best of our knowledge, the case herein presented is the first report of Xp11.2 translocation RCC occurring during pregnancy. Bovio et al [ 23 ] recently reported the case of a 20-year-old pregnant female with placental, bone and retroperitoneal lymph node metastases two years after radical nephrectomy for Xp11.2 translocation RCC, but no evidence of fetal metastasis. Hence, the initial diagnosis of Xp11.2 translocation RCC occurred prior to her pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, the initial diagnosis of Xp11.2 translocation RCC occurred prior to her pregnancy. Bovio et al [ 23 ] stated that given the need for systemic therapy and risk of harm to the fetus, a Cesarean section was performed at 33 weeks gestation. However, they did not specify whether subsequent systemic therapy was given, what specific type of systemic therapy was given (if any), the fate of the bone and retroperitoneal lymph node metastases, and the final patient outcome (whether she was alive with no evidence of disease, was alive with progressive disease, or died of disease).…”
Section: Discussionmentioning
confidence: 99%
“… 2 Genetic abnormalities have also been detected in development of RCC, especially Xp 11.2 translocation, which is the most common mutation. 4 …”
Section: Discussionmentioning
confidence: 99%
“…The characteristics of patients who were diagnosed with RCC during the antenatal period, and the surgical and pregnancy outcomes from 2004 to the present day are shown in Table 1 . 4 , 6 21 …”
Section: Discussionmentioning
confidence: 99%
“…Several case reports and reviews are also available concerning the challenges associated with kidney cancers diagnosed in pregnant women [ 15 – 22 ]. However, there is only limited knowledge about the behavior of metastatic renal cell carcinoma during pregnancy so far [ 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%